ANALISIS POLA PARTISIPASI VERBAL DAN NONVERBAL SISWA DALAM TAHAP THINK PAIR SHARE PADA PEMBELAJARAN SEJARAH DI KELAS XI SMA - Faniska Handayani; Romadi Romadi (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to analyze the patterns of students’ verbal and nonverbal participation at each stage of the Think Pair Share (TPS) learning model in history learning in grade XI of SMA Negeri 7 Semarang. This study employed a descriptive qualitative approach with history teachers and eleventh-grade students as the research subjects. Data were collected through non-participant observation, semi-structured interviews, and documentation. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that students’ participation develops progressively across each stage of TPS. In the think stage, participation appears in the form of cognitive engagement and nonverbal activities such as reading and note-taking. In the pair stage, verbal participation increases through paired discussions that encourage students’ confidence in expressing opinions, asking questions, and responding to peers. In the share stage, participation is reflected in oral communication as well as nonverbal responses such as attention and feedback during presentations. In addition, students’ participation is influenced by internal factors such as self-confidence and learning readiness, as well as external factors including teaching strategies, opportunities to speak, and teacher appreciation. Therefore, the Think Pair Share model is effective in promoting students’ active engagement, both verbally and nonverbally, in history learning.